2017
DOI: 10.1302/1863-2548.11.170008
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-rater reliability of the head-shaft angle in children with cerebral palsy

Abstract: PurposeChildren with cerebral palsy (CP) are at increased risk for hip dislocation. This can be prevented in most cases using surveillance programmes that include radiographic examinations. Known risk factors for hip dislocation include young age, high Gross Motor Function Classification System (GMFCS) level and high migration percentage (MP). The head-shaft angle (HSA) has recently been described as an additional risk factor. The study aim was to determine inter- and intra-rater reliability of the HSA in a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
7
0
4
Order By: Relevance
“…Nevertheless, the good intraobserver and interobserver agreement in our study confirmed the findings of previous studies that HSA measurements are sufficiently reliable in clinical use. 11 , 14 , 21 The strengths of the present study are that it is population-based and longitudinal and that follow-up could be performed in all the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the good intraobserver and interobserver agreement in our study confirmed the findings of previous studies that HSA measurements are sufficiently reliable in clinical use. 11 , 14 , 21 The strengths of the present study are that it is population-based and longitudinal and that follow-up could be performed in all the patients.…”
Section: Discussionmentioning
confidence: 99%
“…A single observer measured the HSA in all 640 hips. Training in the measurement was given and, reassuringly, Hermanson et al [ 10 ] have reported excellent observer reliability for HSA. The present study is based on the radiographs of children at the time of registration into the CPIPS programme and effects of time or intervention on hip centration or HSA were not considered.…”
Section: Discussionmentioning
confidence: 99%
“…El porcentaje de migración de la cabeza femoral se midió según el método de Reimers (4) (figura 1). Dado que la confiabilidad inter e intraobservador es excelente para el ACD con un coeficiente de correlación intraclase (CCI) de 0,92 (95% intervalo de confianza [IC] y un CCI 0,99 (95% IC 0,98-0,99) (19) y la confiabilidad inter e intraobservador del PM es alta (CCI=0,93; 95% IC 0,91-0,95) (20) , la medición fue realizada por un único examinador (21) . En relación con el cálculo de CPUP Score (17) , este se realizó a través de la aplicación para dispositivos móviles, y se introdujeron manualmente los datos solicitados (GMFCS, edad, valor de PM y ACD) para cada cadera evaluada, arrojando como resultado el riesgo de progresión de migración expresado en porcentaje.…”
Section: Pacientes Y Métodounclassified
“…A los pacientes GMFCS nivel III se les realizó una nueva radiografía de pelvis en promedio a los 23 meses (15-28) posteriores a la radiografía índice. A los GMFCS nivel IV se les realizó a los 27 meses (20-40) y a los pacientes GMFCS V se les realizó a los 25 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Gmfcs: Gross Motor Functional Classificationunclassified